Treatment of Chronic Suppurative Otitis Media: A Comparison between Topical, Systemic and Combined Topical-Systemic antibiotics (Ibrahim Cardiac Medical Journal, 2015)
Background and Objectives: The present study was undertaken to determine which of the three treatment modalities (topical, systemic and topical systemic combined) is the best in treating chronic suppurative otitis media (CSOM) in children.Patients & Methods: This comparative clinical trial was conducted prospectively in Dhaka Shisu Hospital, Sher-e-Bangla Nagar, Dhaka over a period of 6 months. We enrolled 92 children with chronic CSOM, aged 5- 12 years, from patients attending at pediatric ENT OPD. The children were randomly assigned to three treatment groups. All parents were advised dry mopping of their children two times daily. The first group (n = 51) received topical ciprofloxacin 4 times daily, the second group received systemic ciprofloxacin only10 mg/kg body weight/day twice daily for 14 days and the third group received both systemic and topical ciprofloxacin. The primary outcome measures were resolution of otorrhoea by 2 - 3 weeks of intervention and healing of tympanic membranes on otoscopy by 8-12weeks of intervention. Hearing levels were assessed by audiometry.Results: Of the three groups of children enrolled in the study, the topical-systemic group was significantly older than the topical and systemic groups (p = 0.003). However, the groups were not different in terms of sex and duration of illness (p = 0.125 and p = 0.191 respectively). The cardinal presentation was otorrhoea. Over half of the children in each group had marginal perforation (p=0.062). Most of the children in each group had mild hearing impairment (p = 0.212). Poor attention and poor academic performance were rarely found. After 2 weeks of treatment, majority of patients in Topical, Systemic and Topical Systemic Combined Group had a successful resolution (92.1%, 95.4% and 94.7%) with no significant difference among the groups (p = 0.641). Time taken for resolution was almost similar among the groups with mean resolution time being 2 weeks (p = 0.313). Difference among the groups regarding hearing impairment was evident with highest impairment being in the Topical and the lowest in the combined group (p = 0.048). Among groups, topical and systemic group had higher improvement of hearing threshold than topical, systemic combined group (p=0.024). The groups were no different with respect to treatment failure (p = 0.595)Conclusions: The study concluded that there was no significant difference in outcome in three modalities of treatment - topical, systemic and topical-systemic combined. So only topical antibiotics will do suffice in the treatment of CSOM, unless there is no sign of complications (like fever and/or pain).Ibrahim Cardiac Med J 2014; 4(1): 27-32